2022
DOI: 10.56499/jppres22.1444_10.5.896
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing activity of Dillenia ochreata leaves ethanol extract in Wistar rats

Abstract: Context: Dillenia ochreata is a medicinal plant used traditionally for scabies treatment. D. ochreata leaves contain secondary metabolites of triterpenoids, phenolics, and steroids that have the potential to accelerate the wound healing process. Aims: To determine the effect of the ethanolic extract of D. ochreata leaves on the speed of healing of burns and incisions. Methods: The test animals were divided into six groups: a positive control group (1% silver sulfadiazine ointment for burns and 10% povidone-iod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…The use of plants in traditional medicine needs to be substantiated by scientific evidence regarding the efficacy, quality standards, and safety of these plants so that traditional medicines are used in accordance with established quality and safety standards. 55 Toxic substances of natural or synthetic origin can affect and damage vital organs in the body, especially the liver, which is susceptible to chemical © 2024 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License attacks due to its involvement in the biotransformation of chemicals.…”
Section: Effect Of Hefe On Some Biochemical Parametersmentioning
confidence: 99%
“…The use of plants in traditional medicine needs to be substantiated by scientific evidence regarding the efficacy, quality standards, and safety of these plants so that traditional medicines are used in accordance with established quality and safety standards. 55 Toxic substances of natural or synthetic origin can affect and damage vital organs in the body, especially the liver, which is susceptible to chemical © 2024 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License attacks due to its involvement in the biotransformation of chemicals.…”
Section: Effect Of Hefe On Some Biochemical Parametersmentioning
confidence: 99%
“…Formula standar dasar basis salep yang digunakan terdiri dari Adeps Lanae sebanyak 15 g dan Vaselin album sebanyak 85 g dan akan dibuat basis salep sebanyak 100 g. Sediaan salep dibuat dengan konsentrasi 10 % b/b dibuat sebanyak 20 g. Salep siap untuk dikemas dengan menggunakan tube atau pot salep (Muharni et al, 2022).…”
Section: Pembuatan Salep Ekstrak Daun Semprawangunclassified
“…5 Muharni et al .6 reported that D. ochreata leaves showed antibacterial activity and healing properties for burns and incision wounds. 7 D. ocheata leaves have been reported to contain sentulic acid and 3βglucopyranosyl-lup-20(29)-en-28-oat, which are active antibacterial agents against E. coli and S. aureus bacteria. Sentulic acid has been reported to have cytotoxic effects on human promyelocytic leukaemia HL-60 cells.…”
Section: Introductionmentioning
confidence: 99%